More parables from the back side - Kalas, J. Ellsworth, 1923- (Nashville : Abingdon, 2005)
This study is an addition to the author's "Back Side" books. Ellsworth Kalas presents new insight into twelve of Jesus' parables by entering them through a unique starting point, a creative retelling, a new "lens," or the eyes of a minor or unsympathetic character. The ebook also will contain a study guide.
More Parables from the Back Side; Dedication; Introduction; 1--The Value of the House; 2--The Man Who Talked with His Soul; 3--What Chance Does an Average Sinner Have?; 4--The Importance of Downward Mobility; 5--The Danger of Being Good and Empty; 6--Risky Business; 7--Miracles Can Be Overrated; 8--Second Chance for a Poor Manager; 9--A Laugh and a Prayer; 10--It Happens While We Sleep; 11--The Importance of Being Dressed for the Party; 12--The Genius of Effective Waiting; Suggestions for Leading A Study of More Parables from the BackSide; MORE PARABLES from the Back Side.
Print version record.
Keywords: Jesus Christ -- Parables -- Sermons; Methodist Church -- Sermons; Sermons, American -- 20th century; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books